Source characterization of ambient fine particles in the Los Angeles basin. Issue 4 (1st July 2007) - Kim, Eugene; Hopke, Philip K
Abstract : Integrated 24 h PM2.5 (particulate matter ≤2.5 µ m in aerodynamic diameter) speciation data collected between 2001 and 2004 at three United States Environmental Protection Agency Speciation Trends Network monitoring sites in the Los Angeles (LA) basin (Simi Valley, downtown LA, and Rubidoux) were analyzed through the application of the positive matrix factorization and seven to nine sources were identified. Secondary particles provided the highest contributions to PM2.5 concentrations (29%–46% for secondary nitrate and 12%–23% for secondary sulfate). Rubidoux, which is located downwind of the LA metropolitan area, and animal feed lots had the highest secondary nitrate concentration, followed by downtown LA. Secondary sulfate concentrations were consistent among three sites. Gasoline vehicle and diesel emissions contributed 12%–22% and 7%–10%, respectively. In addition, other sources such as airborne soil, sea salt, aged sea salt, wood smoke, and incinerator emissions were identified. Key words: source apportionment, Los Angeles basin, speciation trends network, PM2.5 .